Prognostic value of EGFR mutations in surgically resected pathological stage I lung adenocarcinoma. Issue 5 (28th June 2016) - Nishii, Teppei; Yokose, Tomoyuki; Miyagi, Yohei; Daigo, Yataro; Isaka, Tetsuya; Furumoto, Hideyuki; Ito, Hiroyuki; Murakami, Shuji; Kondo, Tetsuro; Saito, Haruhiro; Oshita, Fumihiro; Yamada, Kouzo; et al.
Abstract: Aim: With the advent of the molecular‐targeted therapy, rapid progress has been made in the treatment of advanced or recurrent non‐small‐cell lung cancer (NSCLC). Although surgical complete resection remains the standard and most promising treatment, the clinical significance of epidermal growth factor receptor (EGFR) gene mutations in early‐stage NSCLC remains uncertain. Methods: We investigated the prognostic value of EGFR mutations in surgically resected pathological stage I NSCLC. A total of 388 consecutive patients with NSCLC who underwent complete tumor resection in our hospital from 2006 through 2008 were studied retrospectively. Formalin‐fixed, paraffin‐embedded tissue sections were used to isolate DNA from carcinoma lesions. Mutational analyses of EGFR gene were performed by loop‐hybrid mobility shift assay, a highly sensitive polymerase chain reaction‐based method. Results: Mutations of EGFR were detected in 185 of the 388 patients (47.7%). EGFR mutations were more frequently found in women (110 of 185, 59.5%), adenocarcinoma (183 of 185, 98.9%), patients with no vascular invasion (139 of 185, 75.1%) and nonsmokers (106 of 185, 57.3%). In patients with pathological stage I adenocarcinoma, both overall survival (OS) and disease‐free survival (DFS) were significantly higher in patients with EGFR mutation than in those with wild‐type EGFR . Furthermore, patients with exon 21 mutation have better DFS than those with exon 19 mutation in stage IB adenocarcinoma. Cox's proportional hazard model indicated that EGFR status was an independent variable for predicting the OS and DFS in patients with pathological stage IB adenocarcinoma. Conclusion: Our results suggest that EGFR mutations might be a prognostic factor in patients with pathological stage I lung adenocarcinoma.